(untitled) (Nepalese Journal of Management Research, 2024)
This paper attempts to assess the grammatical errors committed by bachelor first-year management students studying English as a foreign language at Bal Kumari College, Naryangarh in the year 2023. To identify the errors, every student was assigned to write an essay on “The Pros and Cons of Social Media for Students” in about 500 words within 50 minutes. 80 essays were collected through the simple random sampling method, and those essays were checked in depth. All the errors in their essays were collected, identified, classified, explained and analyzed. The results revealed that the most common grammatical errors made by the students involved subject–verb agreement, verb tenses, spellings and punctuation and the causes of the errors were due to intralingual transfer and interlingual transfer.